Penggunaan Aplikasi Instagram dalam Meningkatkan Keaktifan Belajar IPS Peserta Didik SMP Di Jateng - Farid Setyawan; Victor Novianto (UM Purwokerto Press, 2022)
Science and technology continue to develop at an increasingly fast pace. As a form of positive interaction with the development of science and technology, learning activities need to use information technology advance to improve the learning process of students to gain broader insight and experience to achieve 21st-century educational competence. The development of learning media utilizes social media favored by teenagers is expected to be used as a means to display abstract social studies concepts to be seen as concrete. The use of the Instagram application offers various simplicity in presenting material through photos or videos with attractive designs so that it can stimulate the enhancement in the learning activity of students studying social studies study material. This paper aims to find and explain the use of the Instagram application in increasing the social studies learning activity of junior high school students. This study uses a qualitative method with digital observations to the Instagram application and a literature review about student learning activities. The use of the Instagram application that offers various conveniences in presenting material through photos or videos with attractive designs can stimulate the enhancement in the learning activity of students studying social studies study material. Supported by uploaded material that can be accessed anywhere, and for unlimited use. Students can also respond in the form of comments for videos or pictures of other groups.